Signifikansi Sunah dalam Perspektif Said Nursi Bagi Masyarakat Kontemporer - Zaprulkhan Zaprulkhan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
This article discusses Bediuzzaman Said Nursi’s ideas on significance of the Practices of the Prophet (Sunna) for modern people. In the present day, many modern people deal with some problems such as spiritual crisis (existential vacuum), moral degradation, and so on. On the other hand, according to Said Nursi, Practices of the Prophet are all highly beneficial remedies for sicknesses of the spirit, mind, and heart, and particularly for social sicknesses. Accordingly, Practices of the Prophet could give the best solution for modern people problems, both individual sicknesses and social sicknesses. Before proposing Said Nursi’s perspective about significance of sunna, the paper forwards epistemological questions: How are the meaning and function of sunna according to Said Nursi? How are the urgent problems of modern people? What is the significance of Practices of the Prophet for modern people in the view of Said Nursi? The answer of these questions will determine the significance of the Practices of the Prophet in our era and in the future.